Patent foramen ovale and stroke: a possible association with deep vein thrombosis - Raffaele Natale; Luca Maria Capece; Sofia Donnarumma; Pasquale Madonna; Carolina Bologna; Domenico Birra; Antonietta De Sena; Marina Lugarà; Claudio De Luca; Mariavittoria Guerra; Gabriella Oliva; Fabio Granato Corigliano; et al. (Italian Journal of Medicine, 2024)
Patent foramen ovale (PFO) is a congenital heart abnormality consisting of the persistence of a tunnel between the right and left atrium; it is associated with a higher prevalence of strokes. A 52-year-old man was admitted to the emergency room for confusion and deep vein thrombosis with signs of pulmonary embolism; he started treatment with fondaparinux. After admission, there was an ischemic stroke. Blood tests, thrombogenic screening, and infectious diseases showed no alterations. Holter-electrocardiogram, echocardiography, and positron emission tomography-computed tomography were negative except for the presence of PFO. Apixaban and cardioaspirin were started. The surgical treatment was planned, but despite the therapy, there was a new ischemic stroke, so the treatment with mechanical thrombectomy was attempted but failed. The patient was continuing therapy until a new cerebral ischemic episode caused his death; the etiopathogenesis of brain events appears to be associated with the presence of PFO; association with deep venous thrombosis is described in the literature.